2012
DOI: 10.1111/j.1365-2834.2012.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses discuss bedside handover and using written handover sheets

Abstract: Flexible handover methods are implicit within clinical setting issues especially in consideration to nursing teamwork. Good communication processes continue to be fundamental for successful handover processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
87
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 23 publications
3
87
0
3
Order By: Relevance
“…11 The majority of published studies have focused on the implementation of bedside handoffs 3,5,[12][13][14] and nurse perceptions of the process. 9,14,15 Several of the studies that reported on implementation and nurse perceptions also included anecdotal findings of patient perceptions. Webster 16 concluded that patients and their families "appear more relaxed and team members appear highly interactive/communicative with patients during the hand-over process."…”
mentioning
confidence: 96%
“…11 The majority of published studies have focused on the implementation of bedside handoffs 3,5,[12][13][14] and nurse perceptions of the process. 9,14,15 Several of the studies that reported on implementation and nurse perceptions also included anecdotal findings of patient perceptions. Webster 16 concluded that patients and their families "appear more relaxed and team members appear highly interactive/communicative with patients during the hand-over process."…”
mentioning
confidence: 96%
“…In a qualitative survey by Johnson and Cowin (2013), done in Sydney Australia, staff noted that the working environment was less noisy and less disruptive when report took place at the bedside and that fellow staff members overall listened better to report. The aim of the study was to explore nurses' perspectives on the introduction of bedside handover over the use of written report sheets.…”
Section: Advantages Of Bedside Reportingmentioning
confidence: 99%
“…6 Sharing report at the nurses' station puts nurses in close proximity and increases socialization among nurses. Report exchange at the nurses' station can be lengthy because nurses may inject personal opinions about the patient, may try to justify their actions, or may use the report time to air frustrations from the day.…”
mentioning
confidence: 99%
“…More socialization equates to more time spent for shift change. 6 There are drawbacks, however, to bedside report. The nurses use the EHR to review the patient's case at the bedside.…”
mentioning
confidence: 99%
See 1 more Smart Citation